RANCANG BANGUN SISTEM PEMBELAJARAN DENGAN LEARNING MANAGEMENT SYSTEM: Studi Kasus SMAN 107 Jakarta - Maya Cholida Tahta Alfina (2020)
The development of increasingly advanced technology, especially communication and telecommunications technology provides an essential role in the ease that supports humans in everyday life. SMA Negeri 107 Jakarta is one of the public schools that has an "A" accreditation and continues to strive to be able to make all students not only have academic achievements but also have life skills as demanded in this globalization era. In the learning process, SMAN 107 Jakarta carried out using conventional methods which deliver learning material through face to face and also the lack of teacher and student interaction, and not all students can understand the teaching material. To overcome these problems, a learning system developed with a learning management system that aims to help the learning process through learning video content and learning materials as well as exercises. This system can be used on any platform because the system is web-based. The system design method used is the prototyping method and using PIECES analysis. The expected outcome of this research is a learning system with a learning management system that can increase student motivation and also the quality of education at SMAN 107 Jakarta. Keywords: SMAN 107 Jakarta, learning management system, prototyping, PIECES.